Composite Nanofibers: Plasmon‐Enhanced Polymer Photovoltaic Device Performance Using Different Patterned Ag/PVP Electrospun Nanofibers (Adv. Energy Mater. 8/2014). Issue 8 (June 2014) - Chen, Jung‐Yao; Wu, Hung‐Chin; Chiu, Yu‐Cheng; Chen, Wen‐Chang
<x xml:space="preserve">Abstract</x> In article number 1301665, Wen‐Chang Chen and co‐workers report the successful preparation of highly conducting silver (Ag)/poly(vinyl pyrrolidone) (PVP) electrospun nanofibers with controlled Ag crystalline orientation and particle size. The nanofibers are used to significantly enhance the power conversion efficiency of poly(3‐hexyl thiophene) (P3HT):[6, 6]‐phenyl C61‐butyric acid methyl ester (PC61BM) photovoltaic cells. The enhancement is attributed to the conductive network of the crossed pattern and the surface plasmon resonance effect. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>